A catalyst and its preparation method and its application in dehydrogenation of cyclohexanol to cyclohexanone
By adding specific additives and support to the cyclohexanone dehydrogenation catalyst to cyclohexanone, the activity, selectivity and stability of the catalyst are improved, and the problems of low conversion and selectivity of the existing catalysts are solved, thereby achieving an efficient and economical reaction process.
Patent Information
- Application Number
- CN202111523971.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-12-14
AI Technical Summary
The existing cyclohexanol dehydrogenation catalysts have low one-way conversion and selectivity, and insufficient catalyst stability, resulting in high subsequent separation costs and easy catalyst accumulation.
A catalyst with copper as the main active component is used, and additives of Mo, W, Zn oxides and additives of noble metal elements Au and Ag are added, and alkali metal elements Li, Na, K and aluminum oxide, silicon oxide or molecular sieve are combined as support to significantly improve the activity and selectivity of the catalyst and enhance its stability.
The conversion rate and selectivity of the catalyst reached more than 99%. The catalyst was used for 2,000 hours at high aerial speeds, which significantly improved the stability and economicality of the reaction.
Smart Images

Figure BDA0003409221480000111 
Figure BDA0003409221480000112 
Figure BDA0003409221480000121
Abstract
Description
Technical Field
[0001] The present application relates to a catalyst and a preparation method thereof and application in the dehydrogenation of cyclohexanol to produce cyclohexanone, belonging to the field of catalyst materials. Background Art
[0002] Cyclohexanone is an important organic chemical raw material and intermediate. It is the main intermediate for the production of adipic acid and caprolactam, and is also an important industrial solvent. The main synthesis methods of cyclohexanone are oxidation and dehydrogenation. Among them, the dehydrogenation method has high selectivity, simple operation and high safety, and is currently the main method used.
[0003] The dehydrogenation method for producing cyclohexanone is to dehydrogenate cyclohexanol in the presence of a catalyst to produce cyclohexanone. Commonly used cyclohexanol dehydrogenation catalysts include copper catalysts, transition metal catalysts, and precious metal catalysts. Patent CN1094785 discloses a catalyst with α-Al2O3 as a carrier and copper as an active component, wherein the BET surface area of the aluminum oxide is not less than 30 m 2 Patent CN101143326 discloses a composite carrier metal nanocatalyst, including copper as the main catalyst active component, one or more of cobalt, nickel, iron, cerium, and lanthanum as the co-catalyst active component, aluminum oxide as the main carrier, and one or more of magnesium oxide or magnesium nitrate, silicon oxide, calcium oxide or calcium nitrate, zirconium oxide, and molecular sieve as the composite carrier.
[0004] At present, the reported catalysts for cyclohexanol dehydrogenation to cyclohexanone still have low single-pass conversion rate and selectivity, which leads to high subsequent separation costs; at the same time, since the generated product cyclohexanone is prone to polycondensation, it is easy to form carbon deposits on the catalyst, resulting in insufficient catalyst stability. Therefore, further improving the single-pass conversion rate, selectivity and reaction stability of the cyclohexanol dehydrogenation reaction is a problem that needs to be solved in the cyclohexanol dehydrogenation to cyclohexanone method. Summary of the invention
[0005] In order to improve the single-pass conversion rate and reaction stability of the cyclohexanol dehydrogenation reaction to produce cyclohexanone, the present application provides a cyclohexanol dehydrogenation catalyst to produce cyclohexanone. The catalyst described in the present application uses copper as the main active component. Adding at least two first additives of Mo, W, and Zn oxides and a second additive of one of the precious metal elements Au and Ag to the catalyst can significantly improve the activity and selectivity of the catalyst, and the conversion rate and selectivity of the catalyst can reach more than 99%. In order to solve the problem of reaction stability, i.e., life span, of the catalyst in long-term use, adding one of the alkali metal elements Li, Na, and K as a third additive to the catalyst and using a carrier of alumina, silicon oxide or molecular sieve can significantly improve the stability of the catalyst, and no deactivation phenomenon was found in the catalyst after 2000 hours of use under high space velocity conditions.
[0006] In one aspect of the present application, a catalyst for dehydrogenating cyclohexanol to produce cyclohexanone is provided, the catalyst comprising an active component, an auxiliary agent and a carrier;
[0007] The active component includes CuO;
[0008] The auxiliary agent includes a first auxiliary agent, a second auxiliary agent, and a third auxiliary agent;
[0009] The first auxiliary agent is selected from at least two oxides containing the first auxiliary agent element;
[0010] The first auxiliary element is selected from at least two of Mo, W, and Zn;
[0011] The second auxiliary agent is selected from one of the noble metal elements Au and Ag;
[0012] The third auxiliary agent is an alkali metal oxide;
[0013] The alkali metal element in the alkali metal oxide is selected from one of Li, Na and K;
[0014] The carrier is selected from at least one of alumina, silicon oxide or molecular sieve.
[0015] Optionally, the content of the active component is 20-60wt% of the mass of the catalyst, wherein the content of the active component is calculated based on the mass of CuO;
[0016] Optionally, the upper limit of the content of the active component can be independently selected from 30wt%, 40wt%, 50wt%, 60wt%; the lower limit can be independently selected from 20wt%, 30wt%, 40wt%, 50wt%.
[0017] Optionally, the content of the first auxiliary agent is 10-40wt% of the mass of the catalyst, wherein the content of the first auxiliary agent is calculated by the mass of the first auxiliary agent oxide;
[0018] Optionally, the upper limit of the content of the first auxiliary agent can be independently selected from 13wt%, 15wt%, 20wt%, 25wt%, 28wt%, 30wt%, 35wt%, 40wt%, and the lower limit can be independently selected from 10wt%, 13wt%, 15wt%, 20wt%, 25wt%, 28wt%, 30wt%, 35wt%.
[0019] Optionally, the content of the second auxiliary agent is 0.1-1.0 wt% of the mass of the catalyst, wherein the content of the second auxiliary agent is calculated based on the mass of the metal element of the second auxiliary agent;
[0020] Optionally, the upper limit of the content of the second auxiliary agent can be independently selected from 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1.0wt%; the lower limit can be independently selected from 0.1wt%, 0.3wt%, 0.5wt%, 0.6wt%, 0.8wt%.
[0021] Optionally, the content of the third auxiliary agent is 0.5-2.0wt% of the catalyst mass, wherein the content of the third auxiliary agent is calculated by the mass of the third auxiliary agent oxide;
[0022] Optionally, the upper limit of the content of the third auxiliary agent can be independently selected from 1.0wt%, 1.5wt%, 2.0wt%; the lower limit can be independently selected from 0.5wt%, 1.0wt%, 1.5wt%.
[0023] Optionally, the content of the carrier is 20 to 70 wt% of the catalyst mass;
[0024] Optionally, the upper limit of the carrier content can be independently selected from 25wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%; the lower limit can be independently selected from 20wt%, 25wt%, 30wt%, 40wt%, 50wt%, 60wt%.
[0025] Optionally, the first auxiliary agent is composed of composite oxides of two elements among Mo, W and Zn, and the molar ratio of the two first auxiliary agent elements is 0.1 to 5.0:1.
[0026] Another aspect of the present application provides a method for preparing the above-mentioned catalyst, the preparation method comprising:
[0027] (1) dissolving a soluble copper salt in water to prepare a solution A;
[0028] (2) dissolving a soluble salt containing the first auxiliary element in water to prepare a solution B;
[0029] (3) preparing a mixture C with a carrier precursor and water;
[0030] (4) mixing solution A, solution B, and a solution containing a precipitant, and simultaneously adding dropwise to mixture C to form mixture D, and stirring to form a precipitate;
[0031] (5) filtering, washing, drying and calcining the precipitate to obtain a catalyst precursor;
[0032] (6) The obtained catalyst precursor is simultaneously impregnated with the second auxiliary agent and the third auxiliary agent by an equal amount impregnation method, and then dried and calcined to obtain the catalyst.
[0033] Optionally, in the solution A, the concentration of soluble copper salt is 0.5-4 mol / L.
[0034] Optionally, the upper limit of the concentration of the soluble copper salt can be independently selected from 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L; the lower limit can be independently selected from 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L;
[0035] Optionally, the soluble copper salt is selected from one of copper nitrate, copper acetate and copper chloride.
[0036] Optionally, in the solution B, the total concentration of the soluble salt containing the first auxiliary element is 0.5 to 5 mol / L, calculated based on the molar amount of the first auxiliary element.
[0037] Optionally, the upper limit of the total concentration of the first auxiliary agent can be independently selected from 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L, and 5mol / L; the lower limit can be independently selected from 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, and 4.5mol / L.
[0038] Optionally, the carrier precursor is selected from at least one of an alumina carrier precursor, a silica carrier precursor or a molecular sieve carrier precursor;
[0039] Optionally, the alumina carrier precursor is selected from one of aluminum nitrate and hydrated alumina;
[0040] Optionally, the silicon oxide carrier precursor is selected from one of silica sol and fumed silica;
[0041] Optionally, the molecular sieve carrier precursor is selected from one of ZSM-5, Y, Beta, MCM-22, and mordenite;
[0042] Optionally, the mass ratio of the carrier precursor to water is 0.1 to 1:1.
[0043] Optionally, in the solution containing the precipitant, the concentration of the precipitant is 1 to 5 mol / L;
[0044] Optionally, the upper limit of the concentration of the precipitant can be independently selected from 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, 4.5mol / L, and 5mol / L; the lower limit can be independently selected from 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, 3.5mol / L, 4mol / L, and 4.5mol / L.
[0045] Optionally, the precipitant is selected from one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate;
[0046] Optionally, the mixing is performed at 40-80° C., and the pH value of the mixture D is 9.5-12.
[0047] Optionally, the upper limit of the mixing temperature may be independently selected from 50°C, 60°C, 70°C, 80°C; the lower limit may be independently selected from 40°C, 50°C, 60°C, 70°C;
[0048] Optionally, the upper limit of the pH value of the mixture B can be independently selected from 10, 10.5, and 11; the lower limit can be independently selected from 9.5, 10, and 10.5;
[0049] Optionally, the temperature of the calcination I is 300-400° C., the calcination I time is 3h-8h; the calcination I atmosphere is air atmosphere;
[0050] The temperature of the calcination II is 300-400° C., the calcination II time is 3h-8h, and the calcination II atmosphere is air atmosphere.
[0051] Optionally, the upper limit of the calcination temperature I can be independently selected from 350°C and 400°C; the lower limit can be independently selected from 300°C and 350°C;
[0052] Optionally, the upper limit of the calcination time I can be independently selected from 4h, 5h, 6h, 7h, 8h; the lower limit can be independently selected from 3h, 4h, 5h, 6h, 7h;
[0053] Optionally, the upper limit of the calcination temperature II can be independently selected from 350°C and 400°C; the lower limit can be independently selected from 300°C and 350°C;
[0054] Optionally, the upper limit of the calcination II time can be independently selected from 4h, 5h, 6h, 7h, 8h; the lower limit can be independently selected from 3h, 4h, 5h, 6h, 7h.
[0055] Optionally, in step (2), the equal volume impregnation method specifically comprises: using the equal volume impregnation method, impregnating the catalyst precursor obtained in step (1) into a soluble salt solution containing a second auxiliary agent and a soluble salt solution containing an alkali metal element;
[0056] Preferably, the soluble salt containing the second auxiliary agent is selected from chloroauric acid and silver nitrate;
[0057] The soluble salt containing alkali metal elements is selected from lithium nitrate, sodium nitrate and potassium nitrate.
[0058] As a specific implementation method, the preparation method of the catalyst includes the following steps: 1) dissolving a soluble copper salt in water to prepare a solution A; 2) dissolving one or more soluble salts of the first auxiliary agent in water to prepare a solution B; 3) preparing a solution or suspension mixture C with aluminum oxide, silicon oxide or molecular sieve carrier precursor and water; 4) adding solution A, solution B and precipitant solution to mixture C at 40-80°C at the same time, and stirring vigorously to precipitate copper, auxiliary agent and carrier in the mixture. After the addition is completed, the pH value of the mixture is 9.5-11; 5) filtering, washing, drying and calcining the precipitate to obtain a catalyst precursor; 6) impregnating the obtained catalyst precursor with the second auxiliary agent and the third auxiliary agent by an equal amount impregnation method, drying and calcining to obtain a catalyst.
[0059] In another aspect of the present application, a method for preparing cyclohexanone by dehydrogenating cyclohexanol is provided, the method comprising: contacting a raw material containing cyclohexanol with a catalyst to undergo a dehydrogenation reaction to prepare cyclohexanone;
[0060] Wherein, the catalyst is selected from the above catalyst or the catalyst prepared according to the above preparation method.
[0061] Optionally, the raw material further includes an inactive gas;
[0062] Optionally, the inert gas is selected from at least one of nitrogen, helium and argon.
[0063] Optionally, the molar ratio of the cyclohexanol to the inert gas is 1:1 to 15;
[0064] Optionally, the catalyst is used after being reduced in a hydrogen atmosphere at a temperature of 300 to 450° C. for 2 to 6 hours;
[0065] Optionally, the dehydrogenation reaction temperature is 120-160°C, and the mass space velocity of cyclohexanol is 0.1-4.0h -1 .
[0066] Optionally, the upper limit of the dehydrogenation reaction temperature may be independently selected from 130°C, 140°C, 150°C, and 160°C; the lower limit may be independently selected from 120°C, 130°C, 140°C, and 150°C;
[0067] Optionally, the upper limit of the mass space velocity of cyclohexanol can be independently selected from 0.5h -1 , 1.0h -1, 1.5h -1 , 2.0h -1 , 2.5h -1 , 3.0h -1 , 3.5h -1 , 4.0h -1 ; The lower limit can be independently selected from 0.1h -1 , 0.5h -1 , 1.0h -1 , 1.5h -1 , 2.0h -1 , 2.5h -1 , 3.0h -1 , 3.5h -1 ;
[0068] Optionally, the dehydrogenation reaction pressure is normal pressure.
[0069] The beneficial effects of this application include:
[0070] 1) The catalyst provided in the present application has significant activity and selectivity, and solves the problem of reaction stability, i.e., lifespan, of the catalyst during long-term use. No deactivation of the catalyst was found after 2000 hours of use under high space velocity conditions.
[0071] 2) When the catalyst provided in the present application is used in the reaction of cyclohexanol dehydrogenation to produce cyclohexanone, the cyclohexanol conversion rate, cyclohexanone selectivity and catalyst stability are all improved. DETAILED DESCRIPTION
[0072] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0073] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0074] The conversion rate of cyclohexanol and the selectivity of cyclohexanone are calculated as follows;
[0075] Conversion rate of cyclohexanol = (1-mass of cyclohexanol in product / mass of cyclohexanol in raw material) × 100%
[0076] Selectivity of cyclohexanone=(moles of cyclohexanone in the product / (moles of cyclohexanol in the raw material-moles of cyclohexanol in the product)×100%.
[0077] Example 1
[0078] 70.7g of copper nitrate was dissolved in 251.4g of water to prepare solution A, 3.1g of ammonium heptamolybdate and 11.6g of zinc nitrate were dissolved in 40.9g of water to prepare solution B, and 49.9g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a sodium hydroxide solution with a concentration of 2.0mol / L (to a pH value of 9.5) were added dropwise to solution C at 40°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 9.5, and stirring was continued at 40°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.086g of chloroauric acid and 1.37g of sodium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 300°C for 3 hours to obtain catalyst A. The composition of Catalyst A was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0079] Example 2
[0080] 47.2g of copper nitrate was dissolved in 83.8g of water to prepare solution A, 6.1g of ammonium heptamolybdate and 23.3g of zinc nitrate were dissolved in 61.4g of water to prepare solution B, and 60.6g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a sodium hydroxide solution with a concentration of 2.0mol / L (to a pH value of 10) were added dropwise to solution C at 60°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 10.0, and stirring was continued at 60°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.43g of chloroauric acid and 0.27g of potassium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 300°C for 3 hours to obtain catalyst B. The composition of Catalyst B was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0081] Example 3
[0082] 58.9g of copper nitrate was dissolved in 157.1g of water to prepare solution A, 8.0g of ammonium metatungstate and 5.8g of zinc nitrate were dissolved in 15.35g of water to prepare solution B, and 60.4g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a sodium carbonate solution with a concentration of 1.5mol / L (to a pH value of 11.5) were simultaneously added dropwise to solution C at 80°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 11.5, and stirring was continued at 80°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.086g of chloroauric acid and 1.15g of lithium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 400°C for 3 hours to obtain catalyst C. The composition of Catalyst C was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0083] Example 4
[0084] 23.6g of copper nitrate was dissolved in 125.7g of water to prepare solution A, 2.7g of ammonium metatungstate and 9.5g of ammonium heptamolybdate were dissolved in 38.5g of water to prepare solution B, and 80.8g of silica sol was dissolved in 100g of water to prepare solution C. Solution A, solution B and a sodium carbonate solution with a concentration of 2.0mol / L (to a pH value of 11) were added dropwise to solution C at 40°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 11.0, and stirring was continued at 40°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use the equal amount of impregnation method to impregnate 0.86g of chloroauric acid and 0.34g of sodium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 350°C for 3 hours to obtain catalyst D. The composition of Catalyst D was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0085] Example 5
[0086] 35.4g of copper nitrate was dissolved in 188.6g of water to prepare solution A, 5.3g of ammonium metatungstate and 11.6g of zinc nitrate were dissolved in 30.7g of water to prepare solution B, and 99.2g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a sodium carbonate solution with a concentration of 2.0mol / L (to a pH value of 10) were simultaneously added dropwise to solution C at 50°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 10.0, and stirring was continued at 50°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.39g of silver nitrate and 1.07g of potassium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 400°C for 3 hours to obtain catalyst E. The composition of Catalyst E was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0087] Example 6
[0088] 47.1g of copper nitrate was dissolved in 83.8g of water to prepare solution A, 5.3g of ammonium metatungstate and 5.7g of ammonium heptamolybdate were dissolved in 32.4g of water to prepare solution B, and 69.8g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a potassium hydroxide solution with a concentration of 4.0mol / L (to a pH value of 10) were simultaneously added dropwise to solution C at 40°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 10.0, and stirring was continued at 40°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.079g of silver nitrate and 1.73g of lithium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 350°C for 3 hours to obtain catalyst F. The composition of Catalyst F was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0089] Example 7
[0090] 50.7g of copper chloride was dissolved in 94.3g of water to prepare solution A, 2.7g of ammonium metatungstate and 9.3g of zinc nitrate were dissolved in 24.6g of water to prepare solution B, and 25.5g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a potassium carbonate solution with a concentration of 1.5mol / L (to a pH value of 11.5) were simultaneously added dropwise to solution C at 50°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 11.5, and stirring was continued at 50°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.39g of silver nitrate and 0.69g of sodium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 400°C for 3 hours to obtain catalyst G. The composition of Catalyst G was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0091] Example 8
[0092] 50.2g of copper acetate was dissolved in 125.7g of water to prepare solution A, 23.3g of zinc nitrate was dissolved in 61.4g of water to prepare solution B, and 16.6g of ZSM-5 molecular sieve with a silicon-aluminum ratio of 25 was mixed with 100g of water to prepare mixture C. Solution A, solution B and a sodium hydroxide solution with a concentration of 2.0mol / L (to a pH value of 9.5) were simultaneously added dropwise to mixture C at 40°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 9.5, and stirring was continued at 40°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and use an equal amount of impregnation method to impregnate 0.63g of silver nitrate and 0.54g of potassium nitrate aqueous solution. The impregnated sample was dried at 120°C for 12 hours and calcined at 350°C for 3 hours to obtain catalyst H. The composition of catalyst H was measured using an X-ray fluorescence analyzer and the results are listed in Table 1.
[0093] Application Example 1
[0094] 10g of catalyst A was loaded into a fixed bed tubular reactor and reduced at 300℃ for 2 hours under hydrogen atmosphere. Cyclohexanol and nitrogen were introduced into the reactor at a molar ratio of 1.0:1.0 for reaction. The reaction temperature was 150℃ and the pressure was 0.1MPa. The mass space velocity of cyclohexanol was 1.0h -1 After the reaction was continued for 200 hours, the product composition was analyzed by gas chromatography and the reaction results were calculated. The reaction results are listed in Table 2.
[0095] Application Examples 2 to 10
[0096] Catalysts B to H were applied to the dehydrogenation reaction of cyclohexanol using the method of Application Example 1. The reaction conditions and results are listed in Table 2.
[0097] Comparative Example 1
[0098] 70.7g of copper nitrate was dissolved in 251.4g of water to prepare solution A, and 49.9g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A and a sodium hydroxide solution with a concentration of 2.0mol / L were simultaneously added dropwise to solution C at 40°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 9.5, and stirring was continued at 40°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain catalyst I. The composition of catalyst I was measured using an X-ray fluorescence analyzer. The composition of catalyst I is active center CuO and carrier Al2O3, and the ratio is the same as that of catalyst A.
[0099] Comparative Example 2
[0100] 70.7g of copper nitrate was dissolved in 251.4g of water to prepare solution A, 3.1g of ammonium heptamolybdate and 11.6g of zinc nitrate were dissolved in 40.9g of water to prepare solution B, and 49.9g of aluminum nitrate was dissolved in 100g of water to prepare solution C. Solution A, solution B and a sodium hydroxide solution with a concentration of 2.0mol / L (to a pH value of 9.5) were added dropwise to solution C at 40°C and stirred vigorously. After the addition was completed, the pH value of the mixture was 9.5, and stirring was continued at 40°C for 2 hours. The precipitate was then filtered, washed, dried at 120°C for 12 hours, and calcined at 350°C for 3 hours to obtain a catalyst precursor. Take 10g of the catalyst precursor and impregnate 0.086g of chloroauric acid using an equal amount of impregnation method. The impregnated sample was dried at 120°C for 12 hours and calcined at 300°C for 3 hours to obtain catalyst J. The composition and proportion of catalyst J are the same as those of catalyst A except that it does not contain sodium oxide.
[0101] Comparative Example 3
[0102] Catalysts I and J were applied to the dehydrogenation reaction of cyclohexanol using the method of Application Example 1, and the reaction conditions and results are listed in Table 3. Comparing the results in Table 3 with those in Table 1, the conversion rate and selectivity of the catalyst I containing only the active component CuO and the carrier Al2O3 were low, and the stability of the catalyst J without the third additive was poor.
[0103] Table 1 Catalyst compositions prepared in Examples 1 to 8
[0104]
[0105] Table 2 Cyclohexanol dehydrogenation reaction conditions and cyclohexanol conversion and cyclohexanone selectivity of application examples 1 to 10
[0106]
[0107]
[0108] Table 3 Cyclohexanol dehydrogenation reaction conditions and cyclohexanol conversion and cyclohexanone selectivity of Comparative Example 3
[0109] catalyst Reaction temperature℃ <![CDATA[Air speed h -1 > Time Conversion Rate % Selectivity wt% I 150 1.0 200 59.8 96.4 J 150 1.0 200 98.9 99.1 J 150 1.0 500 85.3 94.1
[0110] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A catalyst, characterized in that The catalyst is composed of active components, auxiliary agents and carriers; The active component is CuO; The auxiliary agent is composed of a first auxiliary agent, a second auxiliary agent, and a third auxiliary agent; The first auxiliary agent is at least two of the oxides containing the first auxiliary agent element; The first auxiliary element is selected from at least two of Mo, W, and Zn; The second auxiliary agent is selected from one of the noble metal elements Au and Ag; The third auxiliary agent is an alkali metal oxide; The alkali metal element in the alkali metal oxide is selected from one of Li, Na and K; The carrier is selected from at least one of alumina, silicon oxide or molecular sieve; The content of the active component is 20-60wt% of the mass of the catalyst, wherein the content of the active component is based on the mass of CuO; The content of the first auxiliary agent is 10-40wt% of the mass of the catalyst, wherein the content of the first auxiliary agent is calculated by the mass of the first auxiliary agent oxide; The content of the second auxiliary agent is 0.1-1.0wt% of the mass of the catalyst, wherein the content of the second auxiliary agent is calculated based on the mass of the metal element of the second auxiliary agent; The content of the third auxiliary agent is 0.5-2.0wt% of the catalyst mass, wherein the content of the third auxiliary agent is calculated by the mass of the third auxiliary agent oxide; The content of the carrier is 20-60wt% of the catalyst mass.
2. The catalyst according to claim 1, characterized in that In the first auxiliary agent, the molar ratio of the two first auxiliary agent elements is 0.1-5.0:
1.
3. A method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The preparation method of the catalyst comprises the following steps: (1) Dissolve soluble copper salt in water to prepare solution A; (2) dissolving a soluble salt containing the first auxiliary element in water to prepare solution B; (3) preparing a mixture C with a carrier precursor and water; (4) mixing solution A, solution B, and a solution containing a precipitant, and simultaneously adding dropwise to mixture C to form mixture D, and stirring to form a precipitate; (5) filtering, washing, drying and calcining the precipitate to obtain a catalyst precursor; (6) The obtained catalyst precursor is simultaneously impregnated with the second auxiliary agent and the third auxiliary agent by an equal amount impregnation method, and then dried and calcined to obtain the catalyst.
4. The preparation method according to claim 3, characterized in that: In the solution A, the concentration of soluble copper salt is 0.5-4 mol / L; The soluble copper salt is selected from one of copper nitrate, copper acetate and copper chloride; In the solution B, the total concentration of the soluble salt containing the first auxiliary element is 0.5-5 mol / L, calculated based on the molar amount of the first auxiliary element.
5. The preparation method according to claim 3, characterized in that: The carrier precursor is selected from at least one of an alumina carrier precursor, a silicon oxide carrier precursor or a molecular sieve carrier precursor; The alumina carrier precursor is selected from one of aluminum nitrate and hydrated alumina; The silicon oxide carrier precursor is selected from one of silica sol and fumed silica; The molecular sieve carrier precursor is selected from one of ZSM-5, Y, Beta, MCM-22, and mordenite; The mass ratio of the carrier precursor to water is 0.1-1:
1.
6. The preparation method according to claim 3, characterized in that: In the solution containing the precipitant, the concentration of the precipitant is 1-5 mol / L; The precipitant is selected from one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate; The mixing is performed at 40-80° C., and the pH value of the mixture D is 9.5-12.
7. The preparation method according to claim 3, characterized in that: The temperature of the calcination I is 300-400° C., the calcination time is 2-8 hours, and the calcination atmosphere is air atmosphere; The temperature of the calcination II is 300-400°C, the calcination time is 2-8h, and the calcination atmosphere is air atmosphere; In step (6), the equal amount impregnation method specifically comprises: using the equal amount impregnation method, impregnating the catalyst precursor obtained in step (5) into a soluble salt solution containing a second auxiliary agent and a soluble salt solution containing an alkali metal element; The second auxiliary agent soluble salt is selected from chloroauric acid and silver nitrate; The soluble salt containing alkali metal elements is selected from lithium nitrate, sodium nitrate and potassium nitrate.
8. A method for preparing cyclohexanone by dehydrogenating cyclohexanol, characterized in that: The raw material containing cyclohexanol is contacted with a catalyst to undergo a dehydrogenation reaction to prepare cyclohexanone; The catalyst is used after being reduced in a hydrogen atmosphere at a temperature of 300-450° C. for 2-6 hours; Wherein, the catalyst is selected from the catalyst according to any one of claims 1 to 2 or the catalyst prepared according to the preparation method according to any one of claims 3 to 7.
9. The method according to claim 8, characterized in that The raw materials also include inactive gas; The inert gas is selected from at least one of nitrogen, helium and argon; The molar ratio of the cyclohexanol to the inert gas is 1:1-15; The dehydrogenation reaction temperature is 120~160 o C, the mass space velocity of cyclohexanol is 0.1~4.0 h -1 .
Citation Information
Patent Citations
Ethyl acetate production
CN104066707A
Tert-butyl alcohol dehydrogenation catalyst containing solid potassium and preparation method thereof
CN107597125A